Does work environment impact fertility rate? A comparison between formal and informal sectors in Malaysia / Geetha Subramaniam, Nurfarahain Mohd Saleh - Subramaniam, Geetha; Mohd Saleh, Nurfarahain (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2016)
The fertility rate of Malaysian women has shown a declining trend from having 3 children per woman in 2000 to 1.98 children per woman in 2015. This is an issue of concern for the labour market because declining fertility rates may lead to a stagnant population with other issues such as an ageing population and declining labour force due to low replacement levels. The main purpose of this study is to examine to what extent work environment has an impact on fertility rates in the formal and informal sectors in Malaysia. The study firstly reviews the current trend of women’s fertility rate in Malaysia. It then further examines the working environment of married women in the formal and informal work environment by comparing two different states in Malaysia. Using self-administered questionnaires, 200 married women from the formal sector of Penang and the informal sector of Kelantan were identified through purposive sampling. Data was analysed using descriptive statistics and cross tabulation. The trend review shows an alarming decline in fertility rates in the last ten years. The empirical findings reveal that younger women, with higher educational level, earning a higher income and living in urban areas are more likely to have less number of children.In terms of working environment, women in the informal working sectors tend to have more children. Policy implications in terms of awareness and better work-environment in terms of family friendly policies are recommendations to encourage women to consider having more than one child because if this trend continues, it will have a serious implication on the quantity and quality of the labour force.